PENGEMBANGAN APLIKASI ANDROID BERUPA INTERACTIVE DEMONSTRATION MATERI HUKUM NEWTON - Handy, Handy; Serevina, Vina; Permana, Handjoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The aim of this research was to develop learning media of motion in one dimension to increase analysis capability of students. This research is motivated from discussion with teacher and first data from preliminary questionnaire filled by students about utilazation smartphone to learning especially Newton’s laws. This research was done in senior high school at even semester on 2015-2016. Media which was developed form android application. Therefore, it can demonstrate phenomenon relating with Newton’s laws. Method of this research is Research and Development (R&D) by Borg and Gall and also development design by ASSURE. Collecting validation data of learning media using instrument form questionnaire to media and objectives master. Based on research is expected development of learning media, students can understand Newton’s laws easier and can be accessible anytime and anywhere. Key: Learning media development, Newton’s laws, Android application.